Multidisciplinary perspectives on Zimbabwe's liberation struggle
1 online resource.
Keywords: "This book provides a timely reconceptualization of Zimbabwe's anti-colonial liberation struggle, resisting simple binaries in favour of more nuanced, critical analysis. Most historiographies characterize Zimbabwe's liberation struggle as being defined by simple bifurcations along racial, ethnic, class and ideological perspectives. This book argues that the nationalist struggle is far more complex than such simple configurations would suggest, and that many actors have been overlooked in analysis. The book broadens our understanding by analyzing the roles of a wide range of political figures, organisations, and members of the military, as well as the media and the often overlooked part that women played. Over the course of the book, the contributors also reflect on the ways in which revolutionary figures have been repainted as "sell-outs", in particular by the ZANU PF, and what that means for the country's interpretation of their recent past. Highlighting in particular the expertise of leading scholars from within Zimbabwe, across a range of disciplines, this book will be of interest to researchers of African history, politics, and postcolonial studies"--